OPTIMIZATION AND IN VITRO EVALUATION OF THE RELEASE OF CLASS II DRUG FROM ITS NANOCUBOSOMAL DISPERSION - Al-sakini, Sadeq J.; Maraie, Nidhal K. (International Journal of Applied Pharmaceutics, 2019)
Objective: This work involves investigation and evaluation of the factors that affect the preparation and the release of the model class II drug (erythromycin) to optimize the efficiency of its prepared nanocubosomal dispersion to give very fast initial burst effect within the first hour that can continue for further two hours. Methods: The work involved preparation of ten formulas of cubosomal dispersion by emulsifying different concentrations of glyceryl monooleate (GMO) (lipid content)/surfactant mixtures which were nano-sized and characterized morphologically by Transmission electronic microscopic (TEM), zeta potential, particle size, polydispersity index (pdI), pH, entrapment efficiency, conductivity test, dilution test and in vitro drug release. Results: The selected nanocubosomal formula (F1) showed pH (7.41), particle size (315.05 nm), pdI (0.194), zeta potential (-30.852), entrapment efficiency (91%) and gave a 70% drug release within the first hour of the in vitro test and continued until it gave 96.3% drug release with further 2 h. Conclusion: this work succeeded in preparing optimized cubosomal dispersion for erythromycin using different GMO/poloxamer 407 percent. The optimum formula gave an immediate release of the model drug (erythromycin) and it was ready to be incorporated in any suitable dosage form to give fast onset of action.